Consumer acceptance and purchase intent of a novel low-fat sugar-free sherbet containing soy protein - J. Walker (2018)
This research was designed to develop low-fat sugar-free frozen sherbet products containing an acceptable level of soy protein (SP) recommended by the Food and Drug Administration and to determine consumer sensory profile driving consumer acceptance and purchase intent. Four orange-flavored sherbets were manufactured using four levels of SP isolate (6.0, 6.5, 7.5 and 7.9 g/serving) and evaluated by 140 consumers. Consumers evaluated each sample for acceptability of appearance/color, flavor, sweetness, sourness, texture/mouthfeel and overall liking. Consumers also evaluated overall acceptance and purchase intent of these products. All four formulations were overall different (multivariate analysis of variance, Pr > F = 0.0003). Appearance and sweetness were not used by the consumers to differentiate among the four sherbet formulations. Formulations with 7.9 g and 6.0 g SP were equally liked with the mean overall liking score of 5.60-5.66. Formulation with 6.0 g SP had the highest acceptance (65.0%) and purchase intent (55.7%) after consumers had been informed of soy health benefits. Specifically, overall liking and texture were identified as the two most critical attributes affecting overall acceptance and purchase intent of these products. © 2010 Wiley Periodicals, Inc.